Design and Fabrication of Transparent and Gas‐Tight Optical Windows in Low‐Temperature Co‐Fired Ceramics. Issue 3 (4th February 2013) - Welker, Tilo; Geiling, Thomas; Bartsch, Heike; Müller, Jens
<x xml:space="preserve">Abstract</x> Low‐temperature co‐fired ceramics (LTCC) enable the fabrication of microfluidic elements such as channels and embedded cavities in electrical devices. Hence, LTCC facilitate the realization of complex and integrated microfluidic devices. Examples can be applied in many areas like reaction chambers for synthesis of chemical compounds. However, for many applications it is necessary to have an optically transparent interface to the surroundings. The integration of optical windows in LTCC opens up a wide field of new and innovative applications such as the observation of chemiluminescent reactions. These chemical reactions emit electromagnetic radiation and thus offer a method for noninvasive detection. Thin glasses (≤500 μm) were bonded by thermocompression onto a LTCC substrate. As the bonding agent, a glass frit paste was used. Borosilicate glasses, fused silica as well as silicon were successfully bonded onto LTCC. To join materials with a large coefficient of thermal expansion mismatch (i.e., fused silica and LTCC), it is necessary to limit the heat input to the bond interface. Therefore, a heating structure was integrated into the LTCC substrate beneath the bond interface. This bonding process provides a gas‐tight optical port with a high bond strength.